How do psychosocial stress of the family, early-term birth and early childhood intervention affect the development of children's executive functions? Using Baileys scale III as a measurement for executive functions in children between 0 and 3 years - Törmänen, Minna R. K.; Schaub, Simone; Ramseier, Erich; Koch, Christina; Lanfranchi, Andrea; Kalkusch, Isabelle; Rodcharoen, Patsawee; Neuhauser, Alex; Klaver, Peter (Frontiers in Developmental Psychology, 2025)
Executive functions (EF) are an important predictor of cognitive development. Early measures of EF are however rare. We extracted measurements of EF from the Bayley Scales of Infant and Toddler Development BSID-III, Bayley (2006) at age one, two and three years and investigated the effect of psychosocial stress, early-term birth and early childhood intervention on EF development. Families with psychosocial stress participated in a longitudinal RCT study implementing the home-visiting intervention program Parents-as-Teachers (PAT) (intervention group, N = 121 and control group, N = 111). Birth status (early-term, N = 69; on-term, N = 163) and family stress (high stress, N = 68, low stress, N = 164) were predictors of EF. Family's psychosocial stress had a negative effect of on child's EF development during first three years, while the PAT intervention had a positive effect. Early-term birth had a moderate association with EF development. Implications for early development of EF, early childhood interventions are discussed.